Analisis Pengaruh Penerapan Customer Care Center (C3) Terhadap Kepuasan Pengguna Pada PTIPD UIN Suska Riau dengan Metode E-Servqual - Arabiatul Adawiyah; Febi Nur Salisah (UIN Sultan Syarif Kasim Riau, 2015)
The facilities used to provide services related to the technology used in the UIN Suska Riau, the Center for Information Technology and Data Base (PTIPD) UIN Suska Riau launched the Customer Care Center (C3). The services provided by C3, such as extending the billing internet, enroll for wifi uin Riau Suska, email registration UIN Suska Riau, problems of access IRaise, repair computer networks, as well as service to the problems and improvement of information systems available at UIN Suska Riau. To determine the level of user satisfaction with the services C3, should be a measurement. This needs to be done in order to provide an evaluation of the implementation of C3, so that the leadership can take the decision to make improvements to the service. By using e-servqual (electronic service quality), the PTIPD can know the service desired criteria and also determine whether the user is satisfied with the services provided. In addition, the PTIPD can know which service dimensions that need to be prioritized to be improved in order to increase user satisfaction.Key word: Customer Care Center (C3), Satisfaction, Method E-Servqual (Electronic Service Quality)